Musculoskeletal Symptoms among the Brick Kiln Workers of Kathmandu Valley - Tanweer Mikrani; Naresh Manandhar; Sunil Kumar Joshi (Occupational Health and Safety Society of Nepal, 2017)
Background: Brick kilns may pose threat to the environment and health of the workers and people residing around them. Health problems related to brick kilns are musculoskeletal, respiratory, digestive system, nutritional and skin disorders. Objective of this study was to find out the prevalence of musculoskeletal symptoms (problems) among brick kiln workers of Kathmandu valley. Methods: A cross sectional study was conducted in the brick kilns of Kathmandu valley from February to April 2015. Two hundred (200) workers were selected randomly from the sampled brick kilns of Kathmandu Valley as the exposed group and the equal number of grocery vendors from the surroundings of the brick kilns was included as the control group in term of exposure to ergonomic hazards. The data was collected using Nordic Musculoskeletal Questionnaire. Results: A majority of the respondents were Hindu by religion. The mean age of exposed group was 30.75 years and 33.25 years for control group. Male female ratios were 2.39:1 and 1.94:1 in exposed and control groups respectively. The highest prevalence of musculoskeletal problem was found on Shoulders followed by Lower back, Knee and Neck for exposed group. Conclusion: All musculoskeletal problems were significantly different between exposed and control groups. Compared to the control groups, brick kiln workers had almost 8 times more likely to experience shoulder problem and 7 times more low back pain. All musculoskeletal symptoms at any time during last 12 months were found higher in exposed group compared to the control group, which was statistically significant.